Is there a "retail challenge" to banks' resolvability? What do we know about the holders of bail-inable securities in the Banking Union? - Tatiana Farina; Jan Pieter Krahnen; Irene Mecatti; Loriana Pelizzon; Jonas Schlegel; Tobias Tröger (Leibniz Institute for Financial Research SAFE, 2022)
To ensure the credibility of market discipline induced by bail-in, neither retail investors nor peer banks should appear prominently among the investor base of banks' loss absorbing capital. Empirical evidence on bank-level data provided by the German Federal Financial Supervisory Authority raises a few red flags. Our list of policy recommendations encompasses disclosure policy, data sharing among supervisors, information transparency on holdings of bail-inable debt for all stakeholders, threshold values, and a well-defined upper limit for any bail-in activity. This document was provided by the Economic Governance Support Unit at the request of the ECON Committee.
Keywords: 330; Banking Union; Bailin; Retail Challenge